Pendampingan Pelaku Usaha UMKM Makanan dalam Meningkatkan Promosi Digital Melalui Penggunaan Canva pada Bentoday Jakarta Barat - Pepi Permatasari; Sri Wahyuningsih; Sigit Nurcahyono; Wahyumi Ekawanti (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
MSMEs play a strategic role in supporting the growth and stability of the national economy (Endra et al., 2024), especially in the culinary sector which continues to grow. However, a fundamental problem commonly experienced by MSMEs is the ability to create visually attractive and professional promotional elements. One example is BentoDay, a food business in West Jakarta, which still relies on simple visual promotions through social media without optimal content packaging. This activity aims to develop the digital promotional capacity of participants through program mentoring and training that focuses on creating logos and product catalogs using the Canva application, a digital tool used for easy-to-use visual design purposes that allows even beginners to create posters, banners and social media content (Akbar et al., n.d.). Initial observations, direct training, intensive mentoring, and evaluation of participants' design results are part of the mentoring activity approach. The results of the activity implementation illustrate that participants have the ability to independently produce promotional materials, such as business logos and product catalogs with more attractive and consistent designs. This training not only improves participants' design skills but also has a positive impact on the digital marketing strategy of culinary businesses. MSMEs can improve their competitiveness and increase sales by implementing better design. This approach demonstrates the importance of acquiring digital skills for MSMEs to strengthen their brand identity and expand their consumer reach (Andari, N., Sari, D.P., & Hidayat, 2025). Therefore, using Canva has proven useful for enhancing the competitiveness of MSME digital promotions.